Lateral Extra-articular Tenodesis Reduces Anterior Cruciate Ligament Graft Force and Anterior Tibial Translation in Response to Applied Pivoting and Anterior Drawer Loads. Issue 13 (November 2020) - Marom, Niv; Ouanezar, Hervé; Jahandar, Hamidreza; Zayyad, Zaid A.; Fraychineaud, Thomas; Hurwit, Daniel; Imhauser, Carl W.; Wickiewicz, Thomas L.; Pearle, Andrew D.; Nawabi, Danyal H.
Background: The biomechanical effect of lateral extra-articular tenodesis (LET) performed in conjunction with anterior cruciate ligament (ACL) reconstruction (ACLR) on load sharing between the ACL graft and the LET and on knee kinematics is not clear. Purpose/Hypothesis: The purpose was to quantify the effect of LET on (1) forces carried by both the ACL graft and the LET and (2) tibiofemoral kinematics in response to simulated pivot shift and anterior laxity tests. We hypothesized that LET would decrease forces carried by the ACL graft and anterior tibial translation (ATT) in response to simulated pivoting maneuvers and during simulated tests of anterior laxity. Study Design: Controlled laboratory study. Methods: Seven cadaveric knees (mean age, 39 ± 12 years [range, 28-54 years]; 4 male) were mounted to a robotic manipulator. The robot simulated clinical pivoting maneuvers and tests of anterior laxity: namely, the Lachman and anterior drawer tests. Each knee was assessed in the following states: ACL intact, ACL sectioned, ACL reconstructed (using a bone–patellar tendon–bone autograft), and after performing LET (the modified Lemaire technique after sectioning of the anterolateral ligament and Kaplan fibers). Resultant forces carried by the ACL graft and LET at the peak applied loads were determined via superposition. ATT was determined in response to the applied loads. Results: With the applied pivoting loads, performing LET decreased ACL graft force up to 80% (44 ± 12 N; P < .001) and decreased ATT of the lateral compartment compared with that of the intact knee up to 7.6 ± 2.9 mm ( P < .001). The LET carried up to 91% of the force generated in the ACL graft during isolated ACLR (without LET). For simulated tests of anterior laxity, performing LET decreased ACL graft force by 70% (40 ± 20 N; P = .001) for the anterior drawer test with no significant difference detected for the Lachman test. No differences in ATT were deteced between ACLR with LET and the intact knee on both the Lachman and the anterior drawer tests ( P = .409). LET reduced ATT compared with isolated ACLR on the simulated anterior drawer test by 2.4 ± 1.8 mm ( P = .032) but not on the simulated Lachman test. Conclusion: In a cadaveric model, LET in combination with ACLR transferred loads from the ACL graft to the LET and reduced ATT with applied pivoting loads and during the simulated anterior drawer test. The effect of LET on ACL graft force and ATT was less pronounced on the simulated Lachman test. Clinical Relevance: LET in addition to ACLR may be a suitable option to offload the ACL graft and to reduce ATT in the lateral compartment to magnitudes less than that of the intact knee with clinical pivoting maneuvers. In contrast, LET did not offload the ACL graft or add to the anterior restraint provided by the ACL graft during the Lachman test.